Biomass aerogel with moisture absorption and photo-thermal desorption functions and preparation method thereof
By loading lignosulfonate into bamboo cellulose aerogel, a biomass aerogel with both hygroscopicity and photothermal desorption is prepared, which solves the problems of high energy consumption and structural instability of existing atmospheric water collection materials. , achieving efficient water desorption and self-supporting structure.
Patent Information
- Application Number
- CN202411875918.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-12-19
AI Technical Summary
After absorbing moisture, existing atmospheric water collecting materials need to consume a large amount of electricity and heat energy for water evaporation and desorption, and it is difficult to form a self-supporting structure, which limits its application.
By loading lignosulfonate into bamboo cellulose aerogel, a biomass aerogel with both hygroscopicity and photothermal desorption was prepared using vacuum impregnation and vacuum drying methods.
The excellent moisture absorption effect and light thermal solution absorption ability of biogenic gas gel can be realized. It can trigger hydrolysis and suction through light, greatly reduce the consumption of thermal and electrical energy, and has a stable self -support structure.
Smart Images

Figure CN119331305A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a biomass aerogel with the functions of moisture absorption and photothermal desorption and a preparation method thereof, belonging to the technical field of aerogels. Background Art
[0002] As the global freshwater shortage problem becomes increasingly serious, the development of atmospheric water collection materials provides a new solution to alleviate the shortage of freshwater resources. As a branch of atmospheric water collection materials, hygroscopic materials absorb vapor moisture from the air without relying on surface water sources, and then collect fresh water through heating and condensation, which greatly expands the source of freshwater resources. At the same time, water vapor is the main source of air humidity. Excessive air humidity can cause bacteria to grow on clothes and food and cause them to become damp and moldy, affecting people's quality of life and physical and mental health. Therefore, the development of hygroscopic materials has broad development prospects and important practical significance in alleviating the shortage of freshwater resources and dehumidification.
[0003] Traditional atmospheric water collection materials are mainly calcium chloride and lithium chloride, which have the advantages of high moisture absorption capacity and fast moisture absorption rate. However, after absorbing water, these materials need to consume a lot of electricity and heat energy to drive the evaporation and desorption of water to obtain fresh water. In addition, they have the disadvantages of being non-degradable after being discarded and difficult to form a self-supporting structure, which limits their further application.
[0004] Lignin sulfonate is a natural polymer compound that is mainly derived from the by-products of the papermaking industry. During the papermaking process, the lignin in the wood is treated and partially sulfonated to form lignin sulfonate. The sulfonic acid groups in the molecular structure of lignin sulfonate have good affinity with water molecules, can effectively capture water molecules in the air, and have good hygroscopic properties. More importantly, lignin sulfonate contains a large number of aromatic ring structures, which give it good light absorption performance and photothermal conversion efficiency. It only needs to be irradiated by sunlight to generate heat to trigger water desorption, greatly reducing energy loss. Therefore, the use of lignin sulfonate to prepare biomass hygroscopic materials is very attractive. However, lignin sulfonate generally appears in powder form, and still has the disadvantages of being easy to deliquesce after absorbing moisture and being difficult to form a self-supporting structure. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a biomass aerogel having both moisture absorption and photothermal desorption and a preparation method thereof. The biomass aerogel prepared by vacuum impregnation and vacuum drying method with bamboo cellulose aerogel as a carrier and loading lignin sulfonate has excellent moisture absorption effect and photothermal desorption ability.
[0006] To achieve the above object, the present invention is implemented by adopting the following technical solutions: On the one hand, the present invention provides a biomass aerogel having both moisture absorption and photothermal desorption, including cellulose aerogel, wherein the cellulose aerogel has a porous structure in which lignin sulfonate is loaded; the cellulose aerogel can provide a self-supporting structure for the lignin sulfonate.
[0007] Furthermore, the lignin sulfonate is in powder form, and is one or both of sodium lignin sulfonate and calcium lignin sulfonate.
[0008] Furthermore, the cellulose aerogel is bamboo cellulose aerogel.
[0009] On the other hand, the present invention also provides a method for preparing a biomass aerogel having both moisture absorption and photothermal desorption as described in any one of the above items, comprising: Treating bamboo powder to obtain bamboo cellulose dispersion; Pour the bamboo cellulose dispersion into a mold and freeze-dry to obtain the bamboo cellulose aerogel; preparing a lignin sulfonate solution; The bamboo cellulose aerogel is placed in a lignin sulfonate solution for vacuum impregnation, so that the lignin sulfonate solution is filled into the pores of the bamboo cellulose aerogel. After vacuum drying, a biomass aerogel with both moisture absorption and photothermal desorption is obtained.
[0010] Furthermore, the bamboo powder is processed to obtain a bamboo cellulose dispersion, comprising: a. Put bamboo powder into deionized water and boil it, and then filter to obtain the treated bamboo powder; b. preparing a mixed solution of sodium chlorite and acetic acid, placing the treated bamboo powder into the mixed solution of sodium chlorite and acetic acid, heating and stirring, filtering and washing with water to obtain bamboo powder A; c. Prepare a sodium hydroxide solution, add bamboo powder A into the sodium hydroxide solution, heat and stir, and filter and wash with water to obtain bamboo powder B; d. Prepare a hydrogen peroxide solution, heat bamboo powder B in the hydrogen peroxide solution, heat and stir, and cool to room temperature to obtain a bamboo powder C suspension; e. Sodium hypochlorite and tetramethylpiperidinium oxide were added to the bamboo powder C suspension in sequence, and the pH value of the solution was adjusted to alkaline with sodium hydroxide solution. After stirring for reaction, ethanol was added and allowed to stand, filtered and washed with water, and a dispersion was prepared with deionized water. After ultrasonication, a bamboo cellulose dispersion was obtained.
[0011] Further, in step b, the sodium chlorite and acetic acid mixed solution includes 7-10wt% sodium chlorite solution and 15-20wt% acetic acid solution, the heating temperature is 75-95°C, and the heating time is 3-13h; And / or, in step c, the concentration range of the sodium hydroxide solution is 5-10wt%, the heating temperature is 70-90°C, and the heating time is 3-13h; And / or, in step d, the concentration range of the hydrogen peroxide solution is 15-25wt%, the heating temperature is 75-95°C, and the heating time is 3-10h.
[0012] Furthermore, in step e, the amount of sodium hypochlorite added is 0.2-2% of the total volume of the bamboo powder suspension, the amount of tetramethyl piperidine oxide added is 0.01-2% of the total mass of the bamboo powder suspension, and the amount of ethanol added is 0.5-3% of the total volume of the bamboo powder suspension. The pH value range is 10-10.5, the reaction temperature is 25-40°C, the reaction time is 1-2h, the standing time is 15-24h, and the ultrasonic time is 0.5-1h.
[0013] Furthermore, the concentration range of the bamboo cellulose dispersion is 0.5-2.5wt%.
[0014] Furthermore, the concentration range of the lignin sulfonate solution is 5-50wt%.
[0015] Furthermore, the freeze-drying time is 24-48 hours; and / or the vacuum impregnation time is 0.5-5 hours; and / or the vacuum drying temperature is 60-80° C., and the vacuum drying time is 10-15 hours.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The biomass aerogel of the present invention has both moisture absorption and photothermal desorption functions, is biodegradable, and has a stable self-supporting structure. It can achieve photothermal conversion to trigger water desorption only through light irradiation, greatly reducing the consumption of heat and electrical energy. The preparation method of the present invention is simple and easy to operate. The lignin sulfonate is combined with the bamboo cellulose aerogel, which solves the disadvantage that the lignin sulfonate itself is difficult to form independently, and greatly broadens the application scope of the lignin sulfonate, so that it can be used in the fields of atmospheric water collection and dehumidification. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is a schematic diagram of the sodium lignin sulfonate of Comparative Example 1 of the present invention and the sodium lignin sulfonate after moisture absorption; Figure 2 The sodium lignin sulfonate of Comparative Example 1 of the present invention is heated to 0.35 kW / m 2 Schematic diagram of surface temperature changing with time under light irradiation; Figure 3 Schematic diagram of the bamboo cellulose aerogel of Comparative Example 2 and the bamboo cellulose / sodium lignin sulfonate aerogel of Example 1 of the present invention; Figure 4 The bamboo cellulose aerogel of Comparative Example 2 and the bamboo cellulose / sodium lignin sulfonate aerogel of Example 1 of the present invention are 2 Schematic diagram of surface temperature changing with time under light irradiation; Figure 5 It is a schematic diagram showing the change of moisture absorption over time of the bamboo cellulose aerogel of Comparative Example 2 and the bamboo cellulose / sodium lignin sulfonate aerogel of Example 1 under the condition of 75% humidity; Figure 6 The bamboo cellulose / sodium lignin sulfonate aerogel of Example 1 of the present invention has a moisture absorption rate of 1 kW / m 2 Schematic diagram of the change of water desorption weight over time under light irradiation; Figure 7 This is a schematic diagram showing that the bamboo cellulose / sodium lignin sulfonate aerogel of Example 1 of the present invention is placed in a sealed box with a volume of 10 cm×10 cm×15 cm, and the humidity inside the sealed box changes with time. DETAILED DESCRIPTION
[0018] The present invention will be further described below in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and cannot be used to limit the protection scope of the present invention.
[0019] Example 1
[0020] The embodiment of the present invention provides a method for preparing a biomass aerogel having both moisture absorption and photothermal desorption, comprising the following steps: First, bamboo cellulose aerogel is prepared, specifically including: The bamboo powder is boiled in water to remove water-soluble organic matter, and the treated bamboo powder is obtained by suction filtration.
[0021] The sodium chlorite solution and the acetic acid solution are mixed to obtain a mixed solution of sodium chlorite and acetic acid solution, wherein the sodium chlorite accounts for 7.4wt% and the acetic acid accounts for 18.5wt%.
[0022] The treated bamboo powder was added into a mixed solution of sodium chlorite and acetic acid solution, heated to 90°C, stirred continuously for 12 hours, filtered and rinsed with deionized water to obtain bamboo powder A.
[0023] A 7.4 wt % sodium hydroxide solution was prepared, bamboo powder A was added into the sodium hydroxide solution, and the mixture was heated to 80° C. to react for 12 h. After filtration, bamboo powder B was obtained by washing with deionized water.
[0024] A 18 wt % hydrogen peroxide solution was prepared, bamboo powder B was added to the hydrogen peroxide solution, heated to 90° C. for reaction for 8 h, and cooled to room temperature to obtain a bamboo powder C suspension.
[0025] 3 mL of sodium hypochlorite and 0.2 g of tetramethylpiperidinoxide were added to the bamboo powder C suspension, and the pH was adjusted to 10 with sodium hydroxide solution. The mixture was stirred and reacted at 30°C for 1 h. 10 mL of ethanol was added and allowed to stand for 18 h. The mixture was then filtered and washed with water, and a dispersion was prepared with deionized water. The mixture was ultrasonicated for 0.5 h to obtain a homogeneous 2.5 wt% bamboo cellulose dispersion.
[0026] 3 mL of bamboo cellulose dispersion was poured into a 2 cm × 2 cm × 2 cm square silica gel mold and freeze-dried for 48 h to remove ice crystals to obtain bamboo cellulose aerogel.
[0027] Secondly, sodium lignin sulfonate was selected and prepared into a 50wt% sodium lignin sulfonate solution.
[0028] Finally, the bamboo cellulose aerogel was placed in a sodium lignin sulfonate solution for vacuum impregnation for 0.5 h, and then vacuum dried at 80°C for 15 h to obtain the bamboo cellulose / sodium lignin sulfonate aerogel.
[0029] Example 2
[0030] First, bamboo cellulose aerogel is prepared, specifically including: The bamboo powder is boiled in water to remove water-soluble organic matter, and the treated bamboo powder is obtained by suction filtration.
[0031] The sodium chlorite solution and the acetic acid solution are mixed to obtain a mixed solution of sodium chlorite and acetic acid solution, wherein the sodium chlorite accounts for 7.4wt% and the acetic acid accounts for 18.5wt%.
[0032] The treated bamboo powder was added into a mixed solution of sodium chlorite and acetic acid solution, heated to 90°C, stirred continuously for 12 hours, filtered and rinsed with deionized water to obtain bamboo powder A.
[0033] A 7.4 wt % sodium hydroxide solution was prepared, bamboo powder A was added into the sodium hydroxide solution, and the mixture was heated to 80° C. to react for 12 h. After filtration, bamboo powder B was obtained by washing with deionized water.
[0034] A 18 wt % hydrogen peroxide solution was prepared, bamboo powder B was added to the hydrogen peroxide solution, heated to 90° C. for reaction for 8 h, and cooled to room temperature to obtain a bamboo powder C suspension.
[0035] 3 mL of sodium hypochlorite and 0.2 g of tetramethylpiperidinoxide were added to the bamboo powder C suspension, and the pH was adjusted to 10 with sodium hydroxide solution. The mixture was stirred and reacted at 30°C for 1 h. 10 mL of ethanol was added and allowed to stand for 18 h. The mixture was then filtered and washed with water, and a dispersion was prepared with deionized water. The mixture was ultrasonicated for 0.5 h to obtain a homogeneous 2.5 wt% bamboo cellulose dispersion.
[0036] 3 mL of bamboo cellulose dispersion was poured into a 2 cm × 2 cm × 2 cm square silica gel mold and freeze-dried for 48 h to remove ice crystals to obtain bamboo cellulose aerogel.
[0037] Secondly, calcium lignin sulfonate was selected and prepared into a 50wt% calcium lignin sulfonate solution.
[0038] Finally, the bamboo cellulose aerogel was placed in a calcium lignin sulfonate solution for vacuum impregnation for 0.5 h, and then vacuum dried at 80°C for 15 h to obtain the bamboo cellulose / calcium lignin sulfonate aerogel.
[0039] Comparative Example 1: This comparative example uses sodium lignin sulfonate as the hygroscopic material. Figure 1 As shown, sodium lignin sulfonate is in the form of brown-yellow powder and has certain hygroscopic properties.
[0040] Sodium lignin sulfonate is placed at 0.35kW / m 2 When exposed to light, its surface temperature changes with time as Figure 2 As shown in the figure, due to the aromatic ring structure in sodium lignin sulfonate, it has photothermal conversion performance, at 0.35kW / m 2 After irradiation with high-intensity light source for 600s, the surface temperature of sodium lignin sulfonate rose to 42.4℃.
[0041] Comparative Example 2: This comparative example provides a bamboo cellulose aerogel, and the preparation method thereof comprises: The bamboo powder is boiled in water to remove water-soluble organic matter, and the treated bamboo powder is obtained by suction filtration.
[0042] The sodium chlorite solution and the acetic acid solution are mixed to obtain a mixed solution of sodium chlorite and acetic acid solution, wherein the sodium chlorite accounts for 7.4wt% and the acetic acid accounts for 18.5wt%.
[0043] The treated bamboo powder was added into a mixed solution of sodium chlorite and acetic acid solution, heated to 90°C, stirred continuously for 12 hours, filtered and rinsed with deionized water to obtain bamboo powder A.
[0044] A 7.4 wt % sodium hydroxide solution was prepared, bamboo powder A was added into the sodium hydroxide solution, and the mixture was heated to 80° C. to react for 12 h. After filtration, bamboo powder B was obtained by washing with deionized water.
[0045] A 18 wt % hydrogen peroxide solution was prepared, bamboo powder B was added to the hydrogen peroxide solution, heated to 90° C. for reaction for 8 h, and cooled to room temperature to obtain a bamboo powder C suspension.
[0046] 3 mL of sodium hypochlorite and 0.2 g of tetramethylpiperidinoxide were added to the bamboo powder C suspension, and the pH was adjusted to 10 with sodium hydroxide solution. The mixture was stirred and reacted at 30°C for 1 h. 10 mL of ethanol was added and allowed to stand for 18 h. The mixture was then filtered and washed with water, and a dispersion was prepared with deionized water. The mixture was ultrasonicated for 0.5 h to obtain a homogeneous 2.5 wt% bamboo cellulose dispersion.
[0047] 3 mL of bamboo cellulose dispersion was poured into a 2 cm × 2 cm × 2 cm square silica gel mold and freeze-dried for 48 h to remove ice crystals to obtain bamboo cellulose aerogel.
[0048] The bamboo cellulose aerogel of Comparative Example 2 and the bamboo cellulose / sodium lignin sulfonate aerogel of Example 1 are as follows: Figure 3 As shown, compared with sodium lignin sulfonate powder, bamboo cellulose aerogel has a stable self-supporting structure. After vacuum impregnation and vacuum drying, the bamboo cellulose / sodium lignin sulfonate aerogel is dark brown.
[0049] The bamboo cellulose aerogel of comparative example 2 and the bamboo cellulose / sodium lignin sulfonate aerogel of example 1 were heated at 1 kW / m 2 The surface temperature changes with time under light irradiation Figure 4 As shown in the figure, sodium lignin sulfonate has excellent light-to-heat conversion performance. 2 After irradiation with an intense light source for 1200s, the surface temperature of the bamboo cellulose / sodium lignin sulfonate aerogel can reach 64.9°C, which is significantly higher than that of the bamboo cellulose aerogel, indicating that it has good light absorption performance and photothermal conversion efficiency.
[0050] The moisture absorption of the bamboo cellulose aerogel of Comparative Example 2 and the bamboo cellulose / sodium lignin sulfonate aerogel of Example 1 was changed over time at a humidity of 75%. Figure 5 As shown in Figure 2, the moisture absorption of bamboo cellulose aerogel is almost unchanged, which is due to the presence of sulfonic acid groups in sodium lignin sulfonate. The moisture absorption of bamboo cellulose / sodium lignin sulfonate aerogel reaches 120.79 kg / m 3 , which is much higher than bamboo cellulose aerogel. Then the bamboo cellulose aerogel and bamboo cellulose / sodium lignin sulfonate aerogel after moisture absorption were placed in a 1 kW / m 2 After 3600s of irradiation with high intensity light source, Figure 6 As shown in Figure 2, the desorption capacity of bamboo cellulose / sodium lignin sulfonate aerogel reached 75.38 kg / m 3 , indicating that bamboo cellulose / sodium lignin sulfonate aerogel has excellent photothermal desorption performance.
[0051] In order to test the dehumidification performance of bamboo cellulose / sodium lignin sulfonate aerogel, it was placed in a sealed transparent box (volume 10 cm×10 cm×15 cm), and the humidity in the sealed box dropped from the initial 83.2% to 45.6%.
[0052] In summary, the biomass aerogel prepared by the present invention using bamboo cellulose aerogel as a carrier and loading lignin sulfonate by vacuum impregnation and vacuum drying has excellent moisture absorption effect and photothermal desorption capacity, and can be used in the field of atmospheric water collection and dehumidification.
[0053] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A biomass aerogel having both moisture absorption and photothermal desorption, characterized in that: The invention comprises a cellulose aerogel, wherein the cellulose aerogel has a porous structure and lignin sulfonate is loaded in the porous structure; the cellulose aerogel can provide a self-supporting structure for the lignin sulfonate.
2. The biomass aerogel having both hygroscopic and photothermal desorption properties according to claim 1, characterized in that: The lignin sulfonate is in powder form and is one or both of sodium lignin sulfonate and calcium lignin sulfonate.
3. The biomass aerogel having both hygroscopic and photothermal desorption properties according to claim 1, characterized in that: The cellulose aerogel is a bamboo cellulose aerogel.
4. A method for preparing a biomass aerogel having both hygroscopic and photothermal desorption properties as claimed in any one of claims 1 to 3, characterized in that: include: Treating bamboo powder to obtain bamboo cellulose dispersion; Pour the bamboo cellulose dispersion into a mold and freeze-dry to obtain the bamboo cellulose aerogel; preparing a lignin sulfonate solution; The bamboo cellulose aerogel is placed in a lignin sulfonate solution for vacuum impregnation, so that the lignin sulfonate solution is filled into the pores of the bamboo cellulose aerogel. After vacuum drying, a biomass aerogel with both moisture absorption and photothermal desorption is obtained.
5. The method for preparing biomass aerogel with both moisture absorption and photothermal desorption according to claim 4, characterized in that: The method of treating the bamboo powder to obtain a bamboo cellulose dispersion liquid comprises: a. Put bamboo powder into deionized water and boil it, and then filter to obtain the treated bamboo powder; b. Prepare a mixed solution of sodium chlorite and acetic acid, put the treated bamboo powder into the mixed solution of sodium chlorite and acetic acid, heat and stir, and filter and wash with water to obtain bamboo powder A; c. Prepare a sodium hydroxide solution, add bamboo powder A into the sodium hydroxide solution, heat and stir, and filter and wash with water to obtain bamboo powder B; d. Prepare a hydrogen peroxide solution, add bamboo powder B into the hydrogen peroxide solution, heat and stir, and cool to room temperature to obtain a bamboo powder C suspension; e. Sodium hypochlorite and tetramethylpiperidinium oxide were added to the bamboo powder C suspension in sequence, and the pH value of the solution was adjusted to alkaline with sodium hydroxide solution. After stirring for reaction, ethanol was added and allowed to stand, filtered and washed with water, and a dispersion was prepared with deionized water. After ultrasonication, a bamboo cellulose dispersion was obtained.
6. The method for preparing biomass aerogel with both moisture absorption and photothermal desorption according to claim 5, characterized in that: In step b, the sodium chlorite and acetic acid mixed solution includes 7-10wt% sodium chlorite solution and 15-20wt% acetic acid solution, the heating temperature is 75-95° C., and the heating time is 3-13h; And / or, in step c, the concentration range of the sodium hydroxide solution is 5-10wt%, the heating temperature is 70-90°C, and the heating time is 3-13h; And / or, in step d, the concentration range of the hydrogen peroxide solution is 15-25wt%, the heating temperature is 75-95°C, and the heating time is 3-10h.
7. The method for preparing biomass aerogel with both moisture absorption and photothermal desorption according to claim 5, characterized in that: In step e, the amount of sodium hypochlorite added is 0.2-2% of the total volume of the bamboo powder C suspension, the amount of tetramethyl piperidine oxide added is 0.01-2% of the total mass of the bamboo powder C suspension, the amount of ethanol added is 0.5-3% of the total volume of the bamboo powder C suspension, the pH value range is 10-10.5, the reaction temperature is 25-40° C., the reaction time is 1-2 h, the standing time is 15-24 h, and the ultrasonic time is 0.5-1 h.
8. The method for preparing biomass aerogel with both moisture absorption and photothermal desorption according to claim 4, characterized in that: The concentration of the bamboo cellulose dispersion is in the range of 0.5-2.5 wt %.
9. The method for preparing biomass aerogel with both moisture absorption and photothermal desorption according to claim 4, characterized in that: The concentration of the lignin sulfonate solution is in the range of 5-50 wt %.
10. The method for preparing biomass aerogel with both moisture absorption and photothermal desorption according to claim 4, characterized in that: The freeze drying time is 24-48 hours; and / or, the vacuum impregnation time is 0.5-5 hours; and / or, the vacuum drying temperature is 60-80° C., and the vacuum drying time is 10-15 hours.
Citation Information
Patent Citations
Method for preparing carbon nanofiber aerogel from wood
CN106517144A
Preparation method of wood-based carbon nanotube composite conductive film
CN111647196A
Method for enhancing mechanical properties of nanocellulose membrane by using lignosulfonate
CN112876744A
Preparation method of lignin / nanocellulose aerogel
CN115477785A
Stable moisture absorption photo-thermal core-shell aerogel material and preparation method and application thereof
CN117164962A
Cited By
Bio-based aerogel capable of realizing dual-mode efficient air water collection and preparation method of bio-based aerogel
CN120919979A